Move up or out? Strategies and interventions for small farmers - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
Whether a small farmer should be targeted to “move up” in profitability or “move out” of agriculture depends on whether they face the hard constraints that inhibit profit potential.